Corrosion fatigue lifetime assessment of high-speed railway axle EA4T steel with artificial scratch. (15th March 2021) - Hu, Yanan; Wu, Shengchuan; Withers, Philip J.; Cao, Huatang; Chen, Pei; Zhang, Yajun; Shen, Zhao; Vojtek, Tomáš; Hutař, Pavel
Highlights: The corrosive environment accelerates failure at stresses two thirds of in-air fatigue limit. A conditional probability density function is used for the statistical assessment of fatigue life. The environmentally induced cracks tend to initiate from localized corrosion pitting. The theoretical fatigue limit is obtained based on a low probability event. Abstract: The effects of environment (in air and 3.5 wt% NaCl solution) and artificially-induced surface scratches are investigated on the fatigue properties of railway EA4T (also called 25CrMo4) alloy steel. This steel is found to be markedly sensitive to the chloride-containing environment, with cracking at stresses two thirds of the in-air fatigue limit (+/−326 MPa) under rotating bending (Wöhler) tests. The scratched specimens show even shorter lifetime at stresses below 300 MPa and no fatigue limit is found down to 100 MPa. The fracture surfaces are characterized by the initiation of cracks from multiple sources and intergranular cracking. The fatigue failure of smooth specimens tends to initiate from localized corrosion pitting, while the corrosive environment facilitates crack initiation without pitting for scratched specimens. The fatigue crack growth rate in NaCl solution is slightly higher than that in air. Within the framework of defect-tolerant design, El-Haddad modified Kitagawa-Takahashi (KT) diagrams are constructed to explore the variation in fatigue strength and the defect assessment for both conditions. The modified KT model, which takes the short crack behavior into account, is in better agreement with the experimental results than the original KT diagrams.